After the epidemic: Ongoing declines, stabilizations and recoveries in amphibians afflicted by chytridiomycosis. (February 2017) - Scheele, Ben C.; Skerratt, Lee F.; Grogan, Laura F.; Hunter, David A.; Clemann, Nick; McFadden, Michael; Newell, David; Hoskin, Conrad J.; Gillespie, Graeme R.; Heard, Geoffrey W.; Brannelly, Laura; Roberts, Alexandra A.; et al.
Abstract: The impacts of pathogen emergence in naïve hosts can be catastrophic, and pathogen spread now ranks as a major threat to biodiversity. However, pathogen impacts can persist for decades after epidemics and produce variable host outcomes. Chytridiomycosis in amphibians (caused by the fungal pathogen Batrachochytrium dendrobatidis, Bd) is an exemplar, with impacts ranging from rapid population crashes and extinctions, to population declines and subsequent recoveries. Here, we investigate long-term impacts associated with chytridiomycosis in Australia. We conducted a continent-wide assessment of the disease, reviewing data collected since the arrival of Bd in about 1978, to assess and characterize mechanisms driving past, present and future impacts. We found chytridiomycosis to be implicated in the extinction or decline of 43 of Australia's 238 amphibian species. Population trajectories of declined species are highly variable; six species are experiencing ongoing declines, eight species are apparently stable and 11 species are recovering. Our results highlight that while some species are expanding, Bd continues to threaten species long after its emergence. Australian case-studies and synthesis of the global chytridiomycosis literature suggests that amphibian reservoir hosts are associated with continued declines in endemically infected populations, while population stability is promoted by environmental conditions that restrict Bd impact, and maintenance of high recruitment capacity that can offset mortality. Host genetic adaptation or decreased pathogen virulence may facilitate species recovery, but neither has been empirically demonstrated. Understanding processes that influence Bd-host dynamics and population persistence is crucial for assessing species extinction risk and identifying strategies to conserve disease-threatened species. Highlights: We review the impacts of the disease chytridiomycosis on Australian frogs. Nearly one fifth of Australia's frog species have declined due to chytridiomycosis. Long-term population trajectories of declined species are variable. Environmental refugia and high recruitment are linked with species recovery and stability. Reservoir hosts are associated with ongoing species declines.